A general strategy for facile synthesis of ultrathin transition metal hydroxide nanosheets. Issue 12 (8th January 2019) - Dong, Bing; Ju, Yanmin; Huang, Xiaoxiao; Li, Wei; Ali, Zeeshan; Yin, Hui; Sheng, Fugeng; Hou, Yanglong
Abstract : A general strategy toward the preparation of 2D transition metal hydroxide nanosheets is proposed, which is a 'green chemistry' approach with low demand for equipment, simple operation and low cost. Abstract : A general strategy to produce 2D transition metal hydroxide nanosheets is proposed here. This 'green chemistry' approach requires less equipment, includes simple operation steps and costs little. FeOOH, Co(OH)2, Ni(OH)2, Fe–Mn hydroxide, Co–Zn hydroxide and Ni–Zn hydroxide nanosheets were successfully synthesized through a mechanism of preferentially oriented growth. The produced nanosheets are ultrathin and possess large specific surface area. The representative unmodified FeOOH nanosheets exhibit potential performance for application as a positive contrast agent.